Enhance prodigiosin production under optimal condition in mutant strain of Serratia marcescens QBN - Thanh, Nguyen Sy Le; Nguyen, Thi Hien Trang (Academia Journal of Biology, 2025)
Prodigiosin, a red tripyrrole pigment primarily synthesized by Serratia marcescens, has attracted significant scientific interest due to its wide ranging bioactivities, notably its pro-apoptotic effects on cancer cells. In addition to its anticancer potential, prodigiosin demonstrates antibacterial, antifungal, antibiotic, and immunosuppressive properties, highlighting its relevance for pharmaceutical development. This study aimed to enhance prodigiosin biosynthesis through UV-induced mutagenesis of a wild-type S. marcescens QBN strain, followed by phenotypic selection. A mutant strain, S. marcescens UV1, was obtained through UV irradiation of the wild-type strain and selected based on enhanced pigment production. The results demonstrated a significant improvement in prodigiosin yield from the UV1 mutant compared to the wild-type strain. Specifically, UV1 produced approximately 700 mg/mL of prodigiosin, representing a 1.84-fold increase relative to the wild-type strain’s yield of 380 mg/mL under the same conditions. This enhancement suggests that UV-induced mutagenesis conferred improved biosynthetic efficiency and potentially upregulated the metabolic pathway involved in prodigiosin synthesis. Consequently, S. marcescens UV1 represents a promising candidate for industrial-scale production of prodigiosin in biotechnological and therapeutic contexts.